O estudo da gestão ambiental em instituições de ensino superior, à luz de princípios éticos: um estudo de caso na Faculdade Independente do Nordeste - Fainor - Espinheira, Marcelo José Costa Lima (2014)
In the last decades of the twentieth century, issues related to environmental problems began to gain prominence in the media and in the society, because of the severe degradation caused by the human activities on the environment. Thus for a long time, the earth does not support the unrestrained use of their natural resources and to ensure a better future for the next generations, it is need a change of attitude and behavior of human. In order to assure a better future for the next generations, a change in the attitude of the human being is needed. Thus leaders from different parts of the world have begun to change their stances on the problems caused by the misuse of the natural resources, thinking more ethically towards nature. After all, man is an element of nature and needs it to keep life s continuity. That being so, the higher education institutions should take urgent actions in order to skew the legal standards performing its social role, which means sharing knowledge and preparing citizens with ethical stance and respecting the others and the environment as well, through environmental management actions. In spite of all, the HEIs (higher education institutions) are also responsible for the structure of the future generations. This paper presents a brief study on the practical actions of Environmental Management in the Faculdade Independente do Nordeste (FAINOR), under the ethical principles. During the study, a survey of the environmental initiatives implemented in HEIs (high education institutions) was conducted in order to check the efforts made by them, trying to fit in with the environmental legislation and mitigate the environmental impacts caused by their activities, as well as clarify the underlying values on the decisions adopted in the environmental management.